Women’s Resilience in Dealing with the COVID-19 Pandemic In the Block D5 of Trimulyo Village of Jetis District of Bantul Regency - Siti Aminah (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis paper explores the women’s resilience in dealing with the COVID-19 pandemic in Block D5 of Trimulyo Village of Jetis District of Bantul Regency of Yogyakarta. This study used the qualitative method to prove women's changes from the early days of the COVID-19 pandemic to the new-normal era. The data were collected through an interview process by testing its validity using the triangulation technique. This study results indicated that the initial response of the women in Block D5 admitted that they did not believe in the outbreak because there were no neighbors or close relatives of the respondents whom the COVID-19 had infected. The impact of COVID-19 began to be felt since the implementation of Large-Scale Social Restrictions (PSBB Ind.), which impacted the work cycle. The respondents believed that the virus was a creature of God, so there should have been a way out. Some attempts the women in Block D5 made were convincing themselves and daring to open new businesses, always maintaining health protocols, praying diligently, limiting themselves from watching COVID-19 news to calm their heart and mind, and responding to their economic aspect by increasing productivity to recover the family economy.